2020
DOI: 10.1101/2020.07.31.230870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel isoform ofACE2is expressed in human nasal and bronchial respiratory epithelia and is upregulated in response to RNA respiratory virus infection

Abstract: Angiotensin-converting enzyme 2 (ACE2) is the main entry point in the airways for SARS-CoV-2. ACE2 binding to SARS-CoV-2 protein Spike triggers viral fusion with the cell membrane, resulting in viral RNA genome delivery into the host. Despite ACE2’s critical role in SARS-CoV-2 infection, an understanding of ACE2 expression, including in response to viral infection, remains unclear.Until now ACE2 was thought to encode five transcripts and one 805 amino acid protein. Here we identify a novel short isoform of ACE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 82 publications
5
44
0
Order By: Relevance
“…ITGA5, as previously observed (60)]. Of interest, nasal epithelium, reported to represent the main reservoir of SARS-CoV-2 (61), showed higher levels of short-ACE2 vs. long-ACE2 (24).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…ITGA5, as previously observed (60)]. Of interest, nasal epithelium, reported to represent the main reservoir of SARS-CoV-2 (61), showed higher levels of short-ACE2 vs. long-ACE2 (24).…”
Section: Discussionsupporting
confidence: 73%
“…According to the informations obtained by R&D and Abcam, while MAB933 and Ab15348 are reported to recognize the C-terminus portion of ACE2 (18-740aa and 788-805aa, respectively), Ab108252 is specifically designed to react with a linear peptide located in the N-terminal ACE2 protein sequence (200-300aa). It has been recently reported that a 459 aa short-ACE2 isoform (357-805aa of ACE2 + 10aa at N-terminus) can be co-expressed alongside the full-length ACE2 protein (1-805aa) ( Figure 3A ) (24,25); the short-ACE2 misses part of the N-terminal region targeted by Ab108252 antibody. We observed ACE2 islet-related signal using both MAB933 ( Figure 3B ) and Ab15348 ( Figure 3C ), but the Ab108252 antibody did not show any positivity within the islet parenchyma ( Figure 3D ), raising the possibility that the most prevalent ACE2 isoform within pancreatic islets is the short one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a Myc-DDK-tagged or green fluorescent protein (GFP)-tagged MIRb-ACE2 protein product was detected following overexpression in T24 cells in the same study 24 . Moreover, a separate study 25 reported detection of the putative MIRb-ACE2 protein in primary nasal epithelial cells by western blotting using the same polyclonal anti-ACE2 serum (ab15348), raising the possibility that the protein can indeed be translated.…”
Section: Mirb-ace2mentioning
confidence: 99%